IMPLEMENTASI JOINT BORDER COMMITTEE (JBC) UNTUK PENYELESAIAN SENGKETA PERBATASAN DARAT ANTARA INDONESIA-TIMOR LESTE - Mangku, Dewa Gede Sudika (Jurnal Yuridis, 2018)
Unresolved settlement of land border disputes between Indonesia and Timor Leste is currently in the Noel Besi - Citrana segment, Bidjael Sunan - Oben segment as well as in the Subina segment. The two countries have established the Joint Border Committee as a forum for resolving land boundary disputes that have agreed to use the Treaty 1904 and PCA 1914 as the legal basis for the determination and affirmation of land boundaries between Indonesia and Timor Leste.